2010
DOI: 10.1007/s11116-010-9268-y
|View full text |Cite
|
Sign up to set email alerts
|

Employment status and commute distance of Canadians with disabilities

Abstract: Disabilities, Impairments, Employment status, Commute distance, 2006 Participation and Activity Limitation Survey, Canada,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…At the scale of the metropolitan region where we do not find major differences in the average one-way commute times between workers with and without disabilities, our findings are similar to those reported at national and state levels (Brucker and Rollins 2019; Deka and Lubin, 2012 ; Farber and Páez, 2010 ). What is unusual is that we find slight intraurban differences ( Table 1 ).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…At the scale of the metropolitan region where we do not find major differences in the average one-way commute times between workers with and without disabilities, our findings are similar to those reported at national and state levels (Brucker and Rollins 2019; Deka and Lubin, 2012 ; Farber and Páez, 2010 ). What is unusual is that we find slight intraurban differences ( Table 1 ).…”
Section: Resultssupporting
confidence: 88%
“… Deka and Lubin (2012) compared commute time disparities between New Jersey residents with and without disabilities and found small differences, and Brucker and Rollins (2019) found differences that did not reach statistical significance for a representative sample of the entire U.S. population. In Canada, Farber and Páez (2010) found that disability type did not have a sizeable influence on commute distance.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations